Ladies of liberty : the women who shaped our nation - Roberts, Cokie (Harper, an imprint of HarperCollinsPublishers, 2017)
Shares the stories of remarkable women who shaped American history between 1796 and 1828, including Dolley Madison, Isabella Graham, and Sacajawea.